2018
DOI: 10.1002/hbm.24018
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable meta‐analytic brain networks contribute to coordinated emotional processing

Abstract: Meta-analytic techniques for mining the neuroimaging literature continue to exert an impact on our conceptualization of functional brain networks contributing to human emotion and cognition. Traditional theories regarding the neurobiological substrates contributing to affective processing are shifting from regional- towards more network-based heuristic frameworks. To elucidate differential brain network involvement linked to distinct aspects of emotion processing, we applied an emergent meta-analytic clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 160 publications
2
54
0
Order By: Relevance
“…For instance, a meta-analysis 27 using the Neurosynth database to parcellate the medial frontal cortex showed that the anterior zone, which includes Brodmann's Area 10 and Brodmann's Area 11, is associated with affective processing, including fear processing. Another large-scale meta-analysis using experiments from the Brainmap database 69 showed that Brodmann's Area 10 is associated with attention to emotionally salient information. Consistent with this, a meta-analytic connectivity modeling study 29 showed that that medial orbitofrontal cortex, which includes Brodmann's Area 10 and 11, was coactive with the ventral striatum, amygdala and hippocampus.…”
Section: Co-activation With the Orbitofrontal Cortex Is Linked To Mulmentioning
confidence: 99%
“…For instance, a meta-analysis 27 using the Neurosynth database to parcellate the medial frontal cortex showed that the anterior zone, which includes Brodmann's Area 10 and Brodmann's Area 11, is associated with affective processing, including fear processing. Another large-scale meta-analysis using experiments from the Brainmap database 69 showed that Brodmann's Area 10 is associated with attention to emotionally salient information. Consistent with this, a meta-analytic connectivity modeling study 29 showed that that medial orbitofrontal cortex, which includes Brodmann's Area 10 and 11, was coactive with the ventral striatum, amygdala and hippocampus.…”
Section: Co-activation With the Orbitofrontal Cortex Is Linked To Mulmentioning
confidence: 99%
“…However, this view commonly suggests that multiple neural systems interact in emotion perception and generation, which are modulated by and themselves influence regulatory systems. In terms of neural implementation, it is suggested that these systems rely on large-scale networks (Barrett, 2017;Bressler and Menon, 2010;Riedel et al, 2018;Sripada et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While such an approach targets the specific aspect of regulation, it is not sensitive to the broader interactive process of ER embedded in a hierarchical organization of emotion perception, generation and regulation. Thus, it cannot inform the large-scale networklevel perspective of emotion processing (Barrett, 2017;Bressler and Menon, 2010;Riedel et al, 2018;Sripada et al, 2014). Second, due to inferential limitations of conventional meta-analyses (Poldrack and Yarkoni, 2016) the specificity of brain-cognition associations i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that reward processing studies utilize a variety of complex tasks, task modeling approaches, and theoretical frameworks, it has been difficult to synthesize a quantitative summary of consistent associations between cognitive constructs and brain function. Emerging metaanalytic techniques have proven helpful in synthesizing neuroimaging findings across disperse experimental sites and diverse scientific approaches (Bottenhorn et al, 2019;Bzdok et al, 2015;Bzdok et al, 2013a;Bzdok et al, 2013b;Clos et al, 2013;Eickhoff et al, 2016;Laird et al, 2015;Ray et al, 2015;Riedel et al, 2018). Utilizing these techniques, we aimed to elucidate brain regions, and in turn networks, consistently linked with different aspects of reward processing.…”
Section: Introductionmentioning
confidence: 99%